Expression of a glycosylphosphatidylinositol-anchored ligand, growth hormone, blocks receptor signalling. Issue 6 (29th October 2012) - Guesdon, François; Kaabi, Yahia; Riley, Aiden H.; Wilkinson, Ian R.; Gray, Colin; James, David C.; Artymiuk, Peter J.; Sayers, Jon R.; Ross, Richard J.
Abstract : We have investigated the interaction between GH (growth hormone) and GHR (GH receptor). We previously demonstrated that a truncated GHR that possesses a transmembrane domain but no cytoplasmic domain blocks receptor signalling. Based on this observation we investigated the impact of tethering the receptor's extracellular domain to the cell surface using a native lipid GPI (glycosylphosphatidylinositol) anchor. We also investigated the effect of tethering GH, the ligand itself, to the cell surface and demonstrated that tethering either the ecGHR (extracellular domain of GHR) or the ligand itself to the cell membrane via a GPI anchor greatly attenuates signalling. To elucidate the mechanism for this antagonist activity, we used confocal microscopy to examine the fluorescently modified ligand and receptor. GH–GPI was expressed on the cell surface and formed inactive receptor complexes that failed to internalize and blocked receptor activation. In conclusion, contrary to expectation, tethering an agonist to the cell surface can generate an inactive hormone receptor complex that fails to internalize.